Triaxial Permeability Experimental Study on Deformation and Failure Processes of Single-Fractured Rock Specimens - Taoli Xiao; Mei Huang; Min Gao (Shock and Vibration)
A series of rock-like specimens with specific sizes and fracture inclinations was created in the laboratory. The different effects of seepage pressure on the deformation and failure characteristics between a conventional triaxial compression test and a triaxial permeability test were studied using a servo-controlled testing machine. Furthermore, the change in the permeability of single-fractured specimens was explored based on a triaxial permeability test. The results were as follows. Compared with those observed in the conventional triaxial compression test, the peak stress and corresponding axial strain decrease under seepage pressure in the triaxial permeability test, while the deformation modulus increased. With the increase of fracture length, the peak stress of specimen decreases due to the seepage pressure and the specimen showed tensile failure horizontally. The failure mode of the single-fractured specimens was changed by the seepage pressure. A closed relationship was observed between the failure modes and the permeability-stress curves. A shear failure along the crack surface will occur when the permeability abruptly changed later than the peak stress point. The dramatic change in the permeability indicated that the permeability channel was extended or new seepage paths were created. These conclusions can provide a valuable theoretical reference for the numerical simulation of excavation and design in stability analysis of jointed rock masses.